ENT 530 Social Media Portfolio: Saudagar Kunyah / Isa Ramli - Ramli, Isa (2021)
Saudagar Kunyah is a small partnership business focus on food especially on chips type of snack or product. There is various type of chips offered especially for people who love to eat chips as snack during work or their free time. This kind of snack is also suitable to be eaten with family members and friend, during variety of event, reunion, etc. Our business also offered chips for an affordable price so that people can enjoy our variety kind of chips. Our product is suitable for people with any kind of age and it is also affordable for people with any kind of income. Saudagar Kunyah focus on the quality and the affordability of the price of our products to attract potential customer. Maintaining the quality and the price of our product is important to maintain our relationship with the customer. Many people would be attracted when a good quality product is being sold in an affordable price because it benefits them a lot. Our business was first created by my business partner, Afham Bin Sukurdin and I was invited to join his business venture. We created the Facebook Page to expose our business product online and to gain customer especially people from Selangor. Media social platform is important to promote and expand our business and to gain more potential customer. We would also like to expand our business around Malaysia in the future.